PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN FILM DOKUMENTER TERHADAP HOTS SISWA - Rizki Azhar Nur Farid; Ati Sadiah; Kurniawan Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The problem in this study is the low level of students’ Higher Order Thinking Skills (HOTS) in Economics. This study aims to determine the effect of implementing the Problem Based Learning (PBL) model assisted by documentary films on improving students’ HOTS. The research method used was quasi-experimental with a nonequivalent control group design. The sample consisted of 68 grade XI students divided into experimental and control classes. The instrument used was an essay test based on HOTS indicators according to Noviana: problem solving, decision making, critical thinking, and creative thinking. The results showed a significant improvement in HOTS in the experimental class with a significance value of 0.000. Therefore, the PBL model with documentary film is effective in enhancing students’ HOTS.